The Concept of Infertility in Ayurveda:A Review - Meher, Krishna; Meher, Sudeshna (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda has a holistic approach to most diseases. It is the same in the case of fertility treatments too. Many factors affect both men’s and women’s fertility these days, including stress, pollution, poor diet, and a sedentary lifestyle, to name a few. To ensure that the mind and body are in the best possible condition to procreate, it’s critical to cleanse the body of toxins and nourish it with the right nutrients. Despite years of trying, one out of every seven couples have problems conceiving. This is due to a variety of social, emotional, and physiological variables. Around 25% of instances may be unexplained infertility, in which both men and women have no recognized aetiology. Fertility rates and population growth rates are steadily declining over the world, particularly in developed countries. Present paper aims to throw some light on the concept of infertility as per the concepts of Ayurveda.